Teaching English in Elqubba primary schools: Issues and directions - Muftah Hamed; Tahar Fadhil (Intelektual Pustaka Media Utama, 2019)
The Libyan Ministry of Education has taken important steps to introduce English from the 1st grade (age 6) since autumn semester 2018/2019, yet without taking into considerations the issues that will be faced in teaching English in primary schools. This study, therefore, aimed to identify the issues encountered in the teaching of English from the 1st grade to the 4th grade in primary schools in Elqubba, a city in Eastern Libya and how to overcome these issues. Data were collected through focussed observations and semi-structured interviews. The findings revealed that crowded classrooms, lack of teaching tools and equipments, insufficient exposure to the target language, extensive use of Arabic language, some deficiencies in